2005
DOI: 10.1111/j.1365-2702.2005.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Supporting learners in clinical practice: capacity issues

Abstract: Increases in learner numbers and National Health Service modernization have had an impact on clinical placements' capacity to support learning, and potentially, on learners' achievements in practice. Findings from this study are thus important in evaluating the impact of these policy initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 35 publications
(53 reference statements)
7
61
1
1
Order By: Relevance
“…In a previous study, clinical nurse managers perceive this support to be excellent (Begley and Brady, 2002). Students however held the opposite view in this study and in other studies (Ross and Clifford, 2002;Hutchings et al, 2005). Gerrish (2000) found that newly qualified nurses had experienced greater support than a similar cohort in 1985 in the UK.…”
Section: Inadequate Preparationcontrasting
confidence: 44%
See 2 more Smart Citations
“…In a previous study, clinical nurse managers perceive this support to be excellent (Begley and Brady, 2002). Students however held the opposite view in this study and in other studies (Ross and Clifford, 2002;Hutchings et al, 2005). Gerrish (2000) found that newly qualified nurses had experienced greater support than a similar cohort in 1985 in the UK.…”
Section: Inadequate Preparationcontrasting
confidence: 44%
“…Ethical approval or voluntary participation in the latter survey was not discussed nor the demographic detail of this group, which was not limited to novices. Hutchings et al (2005) have explored how student nurses are supported with regard to capacity and suitability of the environment to do so. Purposive sampling was chosen, including those with an interest in educational issues.…”
Section: Personnel To Support Students and Qualified Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…For kontaktsykepleierne vil det ofte vaere slik at de befinner seg i en situasjon preget av dilemmaet mellom å bruke tid på studentene, og det handlingspresset pasientenes behov innebaerer. Tid er et gjennomgående problem for sykepleiere som har blitt tildelt et veiledningsansvar for sykepleierstudenter (Hutchings, Williamson & Humphreys 2005).…”
Section: Språk Innhold Og Tenkningunclassified
“…Support for students whilst undertaking placement-based learning is advocated throughout the literature (Andrews et al 2005;Hutchings, Williamson, and Humphreys 2005;Levett-Jones and Bourgeois 2011). However, little literature exists on how to support such a period of practice (Neill and Mulholland 2003).…”
Section: Student Supportmentioning
confidence: 99%